Stenting of Coarctation of Aorta in a Post Device Closure of Patent Ductus Arteriosus and Balloon Coarctoplasty patient: A Case Report (Cardiovascular Journal, 2016)
Intravascular stent treatment of coarctation of Aorta has proved successful in 96-98% cases. The decision as to which method should be utilized for treatment of coarctation, out of the option of surgical, balloon angioplasty and stent implantation is still controversial in our center. We do balloon angioplasty for majority of cases as stents are expensive and patients are very young. Here we are reporting a case who had device closure of patent ductus arteriosus (PDA) 3 month ago along with balloon angioplasty of coarctation. But patient developed re coarctation within one month and then intravascular stent was implanted.Cardiovasc. j. 2016; 9(1): 64-67